2006
DOI: 10.4049/jimmunol.176.1.640
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine Suppresses Ezrin-Radixin-Moesin-Dependent T Cell-APC Conjugation through Inhibition of Vav Guanosine Exchange Activity on Rac Proteins

Abstract: We have shown recently that the azathioprine metabolite 6-Thio-GTP causes immunosuppression by blockade of GTPase activation in T lymphocytes. In the present study, we describe a new molecular mechanism by which 6-Thio-GTP blocks GTPase activation. Although 6-Thio-GTP could bind to various small GTPases, it specifically blocked activation of Rac1 and Rac2 but not of closely related Rho family members such as Cdc42 and RhoA in primary T cells upon stimulation with αCD28 or fibronectin. Binding of 6-Thio-GTP to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
159
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(169 citation statements)
references
References 68 publications
9
159
0
1
Order By: Relevance
“…The GEF Vav2 is unable to exchange 6-T-GDP, preventing reactivation of Rac1. These data indicate that 6-T-GDP may irreversibly inhibit Rac1, including its downstream signaling (11).…”
mentioning
confidence: 72%
See 4 more Smart Citations
“…The GEF Vav2 is unable to exchange 6-T-GDP, preventing reactivation of Rac1. These data indicate that 6-T-GDP may irreversibly inhibit Rac1, including its downstream signaling (11).…”
mentioning
confidence: 72%
“…To date, there is limited information on the exact cellular mechanism underling the immunosuppressive properties of azathioprine in T cells (10,11) and monocytes/macrophages (33). Poppe et al (11) demonstrated that azathioprine and its metabolites 6-MP and 6-T-GTP have the ability to potently block the activity of Rac1 and Rac-2 in T cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations